2015
DOI: 10.1038/bjc.2015.19
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression signature of oral squamous cell carcinoma: functional role of microRNA-26a/b in the modulation of novel cancer pathways

Abstract: Background:MicroRNAs (miRNAs) have been shown to play major roles in carcinogenesis in a variety of cancers. The aim of this study was to determine the miRNA expression signature of oral squamous cell carcinoma (OSCC) and to investigate the functional roles of miR-26a and miR-26b in OSCC cells.Methods:An OSCC miRNA signature was constructed by PCR-based array methods. Functional studies of differentially expressed miRNAs were performed to investigate cell proliferation, migration, and invasion in OSCC cells. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 41 publications
2
105
0
Order By: Relevance
“…MiR-26b also displayed low levels of expression in a human embryonic stem cell line (HUES-17) and in a colorectal cancer cell line with a high metastatic potential (LoVo) [64]. Loss of miR-26b also enhanced migration and invasion in oral squamous cell carcinoma [65]. Additionally, miR-26b expression in neural stem cells was found to be induced during their differentiation into neurons in vivo [66].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-26b also displayed low levels of expression in a human embryonic stem cell line (HUES-17) and in a colorectal cancer cell line with a high metastatic potential (LoVo) [64]. Loss of miR-26b also enhanced migration and invasion in oral squamous cell carcinoma [65]. Additionally, miR-26b expression in neural stem cells was found to be induced during their differentiation into neurons in vivo [66].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for PCR quantification was previously described (13,1820). The expression levels of miR-375 (assay ID: 000564; Applied Biosystems, Foster City, CA, USA) were analyzed by TaqMan qRT-PCR assays (TaqMan MicroRNA assays; Applied Biosystems) and RNU48 (assay ID: 001006) was used for normalization.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, numerous studies have shown that miRNAs are aberrantly expressed in several cancers, including ESCC (6,8). Using miRNA expression signature analyses, we have sequentially identified tumor-suppressive miRNAs and shown that these miRNAs mediate novel cancer networks (913). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34] Our past study showed that downregulation of these miRNAs enhanced cancer cell migration and invasion in oral cancer through direct regulation of TMEM184B. 35 In PCa, EZH2, a histone-lysine N-methyltransferase enzyme, was directly regulated by miR-26a and miR-26b. 36 Overexpression of EZH2 is observed in several cancers and contributes to cancer aggressiveness.…”
Section: Discussionmentioning
confidence: 99%